Synthesis and antibacterial activity of some novel thieno[2,3-c]pyridazines using 3-amino-5-phenyl-2-ethoxycarbonylthieno[2,3-c]pyridazine as a starting material - Ahmed S.N. Al-Kamali; Ahmed A. Al-Hazmi; Mohammed H.M. Alhousami; Mokhtar A. Al-Masany (Arabian Journal of Chemistry, 2014)
3-Amino-5-phenyl-2-ethoxycarbonylthieno[2,3-c]pyridazine (6) was prepared by reaction of 4-cyano-6-phenylpyridazine-3(2H)-thione (4) with ethyl chloroacetate in the presence of sodium ethoxide. Hydrazinolysis of compound 6 yielded the corresponding carbohydrazide, (9) which on treatment with acetylacetone and ethyl acetoacetate produced the novel thieno[2,3-c]pyridazines (10 and 11). Treatment of compound 9 with nitrous acid yielded the corresponding carboazide (13), which upon boiling in toluene furnished imidazo[4′,5′:4,5]thieno[2,3-c]pyridazine (15). Pyrimidothienopyridazines (16–18) were achieved by cyclocondensation of compound 9 with some reagents, namely acetic anhydride, formic acid, and triethyl orthoformate. The newly synthesized compounds were confirmed by elemental analyses and spectral data. The antibacterial activities of the new compounds were also evaluated.